A Ritual Geology : Gold and Subterranean Knowledge in Savanna West Africa. - d'Avignon, Robyn (Durham : Duke University Press, 2022)
Robyn d'Avignon tells the history of West Africa's centuries-old indigenous gold mining industries and its shared practices, prohibitions, and cosmological engagements.
Cover -- Contents -- Acknowledgments -- Orthographic Notes -- Abbreviations -- Introduction. Geology and West African History -- 1. A Tale of Two Miners in Tinkoto, Senegal, 2014 -- 2. West Africa's Ritual Geology, 800-1900 -- 3. Making Customary Mining in French West Africa -- 4. Colonial Geology and African Gold Discoveries -- 5. Mineral Mapping and the Global Cold War in Sénégal Oriental -- 6. A West African Language of Subterranean Rights -- 7. Race, Islam, and Ethnicity in the Pits -- Conclusion. Subterranean Granaries -- Glossary -- Notes -- Bibliography -- Index -- A -- B -- C -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books